2015
DOI: 10.3923/ajft.2015.93.99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some Plants and Pesticides on Acetylcholinesterase

Abstract: The principal role of acetylcholinesterase (AChE)is the termination of nerve impulse transmission at the cholinergic synapses by rapid hydrolysis of acetylcholine (ACh). Inhibition of AChE serves as a strategy for the treatment of Alzheimer's Disease (AD). Several acetylcholinesterase inhibitors (AChEIs) are used for the symptomatic treatment of AD A potential source of AChE inhibitors is certainly provided by the abundance of plants in nature. The aim of this article is study the effect of some plants and pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Regarding its mechanism of action, coumaran may also be compared to the monoterpene 1,8-cineole [ 31 ] or other synthetic pesticides such as organophosphates and carbamates [ 32 ]. Moreover, Khorshid, et al [ 33 ] have presented the inhibitory activity of methanolic extract from Cassia fistula L. (Fabaceae) roots and proposed the indole alkaloids as new potential active agents. However, it should be noted that many essential oils and terpenes therefrom have demonstrated anti-AChE activity in vitro, but their contribution to insect mortality is questionable [ 34 ].…”
Section: Plant Derived Insecticides That Affect the Nervous Systemmentioning
confidence: 99%
“…Regarding its mechanism of action, coumaran may also be compared to the monoterpene 1,8-cineole [ 31 ] or other synthetic pesticides such as organophosphates and carbamates [ 32 ]. Moreover, Khorshid, et al [ 33 ] have presented the inhibitory activity of methanolic extract from Cassia fistula L. (Fabaceae) roots and proposed the indole alkaloids as new potential active agents. However, it should be noted that many essential oils and terpenes therefrom have demonstrated anti-AChE activity in vitro, but their contribution to insect mortality is questionable [ 34 ].…”
Section: Plant Derived Insecticides That Affect the Nervous Systemmentioning
confidence: 99%
“…Recent researches showed that AChE inhibitors not only alleviate the cognitive defect of AD patients by elevating acetylcholine (ACh) levels, but also act as disease modifying agents by preventing the early step of AD, the assembly of β -amyloid peptide (Aβ) into amyloid plaque 23 , 24 . Nevertheless, some obvious adverse effects including nausea and vomiting, decreased appetite, weight loss, hepatotoxicity or problems associated with bioavailability were also reported for these drugs 25 28 . Additionally, these drugs are only focused on the symptomatic aspects but cannot prevent, halt or reverse the progression of the disease 14 .…”
Section: Introductionmentioning
confidence: 99%
“…[70] Thus, R. serpentina was an effective candidate as a source of antioxidants and AChE inhibitors. [74] In another study by Saharia et al, reserpine efficacy in the treatment of AD was evaluated. [75] They reported that AChE is responsible for increasing the reserpine mediated lifespan [76] and reduction in Aβ toxicity.…”
Section: R Serpentina and Neurodegenerative Diseases (Ndd)mentioning
confidence: 99%